Protocol for identifying and characterising critical physical tasks in the military: Development and validation. - Tseli, Elena; Monnier, Andreas; LoMartire, Riccardo; Vixner, Linda; Äng, Björn; Bohman, Tony (Work, 2024)
BACKGROUND: When establishing Physical Employment Standards, validity is dependent on the correct identification and characterisation of critical job tasks. OBJECTIVE: To develop and validate a standardised protocol for the identification, characterisation, and documentation of critical physical job tasks in military occupational specialities in the Swedish Armed Forces (SwAF), and propose a definition of critical physical job tasks for use in the SwAF. METHODS: A protocol was drafted with three content domains, including a preliminary definition. Protocol content validity was iteratively assessed in two consecutive stages where ten subject experts rated relevance and simplicity. A consensus panel revised the protocol after each stage. Content validity index (CVI) was calculated as item-CVI (I-CVI) per each feature and as scale average (S-CVI/Ave) per content domain. Acceptable content validity thresholds were 0.78 and 0.90, respectively. RESULTS: The validated protocol consisted of 35 items with an I-CVI≥0.90 and≥0.80 for relevance and simplicity, respectively. The S-CVI/Ave was 0.97 for relevance and 0.98 for simplicity. The protocol was language reviewed, reorganised for easy use, and approved by the consensus panel. The final protocol includes: background and aim of the protocol, the accepted generic and critical physical job task definitions, protocol instructions, subject expert-qualifications, job task source and characteristics. CONCLUSION: A standardised protocol for identification and characterisation of critical job tasks in SwAF military occupational specialties was developed. The protocol content was rated relevant and simple by experts and will be of importance in future work establishing physical requirements in the SwAF.